Advances in geocomputation : Geocomputation 2015 -- the 13th International Conference - Griffith, Daniel A.; Chun, Yongwan; Dean, Denis J. (Advances in geographic information science., 2017)
This book contains refereed papers from the 13th International Conference on GeoComputation held at the University of Texas, Dallas, May 20-23, 2015. Since 1996, the members of the GeoComputation (the art and science of solving complex spatial problems with computers) community have joined together to develop a series of conferences in the United Kingdom, New Zealand, Australia, Ireland and the United States of America. The conference encourages diverse topics related to novel methodologies and technologies to enrich the future development of GeoComputation research.- Resumé vydavatel